Implementation of a 1-Day Living Kidney Donor Evaluation Program: A Qualitative Analysis of Donor Candidate and Stakeholder Perspectives - Lindsay Reid; Shreepriya Mangalgi; Gurraman Mann; Cynthiya Gnanaseelan; Natasha Hudek; Jamie Brehaut; Jessica McDougall; Heather Badenoch; Ariana Noel; Edward G. Clark; Kevin D. Burns; Greg Knoll; et al. (Kidney International Reports)
Introduction: A lengthy donor evaluation process hinders living donor kidney transplantation (LDKT). At The Ottawa Hospital, 1-day evaluation process was recently developed, with a goal to accelerate the determination of donor suitability. The major objective of this study was to solicit feedback from donor candidates and key stakeholders who participated in the 1-day living kidney donor evaluation process, to determine the program’s acceptability and factors influencing its implementation elsewhere. Methods: Semi-structured interviews were conducted with donor candidates who participated in the 1-day living kidney donor evaluation process, and with stakeholders who are instrumental to the implementation strategy. Interviews were conducted via videoconference or by telephone from May 2022 to December 2022. Directed content analysis was conducted using 2 unique frameworks for stakeholder and donor candidate interviews. Results: Our study included 13 stakeholders and 18 donor candidates, of whom 16 (89%) were women and 7 (39%) proceeded to kidney donation. Eighteen (100%) perceived the process to be both time-effective and cost-effective, due to reduced travel and missed work time. Thirteen (72%) felt that the 1-day evaluation may accelerate determination of donor suitability. Sequential virtual sessions with a nurse and social worker in advance of the evaluation day were seen as providing critical education and support. Among stakeholders, 11 (85%) emphasized donor candidate care and faster candidacy determinations. Conclusion: The 1-day evaluation process was preferred by most donor candidates, and was perceived as time-effective and cost-effective by most interviewees. An expedited, 1-day evaluation may accelerate determination of donor suitability and improve LDKT rates.